A study on the use of tea (Camellia sinensis) flower extract in the feed of rainbow trout (Oncorhynchus mykiss): Growth, body composition, and hematological blood parameters - Karabulut HΑ; Günal, Ş; Köse, Ö (Journal of the Hellenic Veterinary Medical Society, 2025)
This study investigated the effects of supplementing rainbow trout (Oncorhynchus mykiss) feed with tea flower (Camellia sinensis) extract (TFE) on growth performance, body composition and haematological blood parameters. A total of 360 rainbow trout with a mean length of 12.2±0.21 cm (min 11.5 cm; max 13.00 cm) and a mean weight of 20.3±0.26 g (min 18.00 g; max 22.00 g) were used in the study. Thirty fish were placed in each of 12 fibreglass tanks, each with a volume of 100 L (80 L adjusted), a flow system (water flow of 9 L/min) and air support. In the study, a commercial trout feed was supplemented with TFE and 4 different experimental groups (0 ml/kg (Control), 10 ml/kg (TFE-10); 20 ml/kg (TFE-20) and 40 ml/kg (TFE-40) tea flower extract/kg feed) with 3 replicates were formed and randomly distributed. The results showed that final body weight, weight gain, weight gain rate, specific growth rate, feed conversion ratio, protein efficiency, survival and meat yield were significantly higher in the TFE-10 group compared to the control group (P<0.05). TFE supplementation was determined to increase the protein ratio and decrease the fat ratio in the fish flesh composition. Haematological blood parameters, except for PLT, were significantly higher in the TFE-10 group compared to the control group at the end of the study (P<0.05). Based on the results of the cubic polynomial regression, it was calculated that a mean TFE level of 12.3±3.81 ml/kg was suitable for optimal fish growth